MODEL PENINGKATAN PRODUKSI PERKEBUNAN KARET SEBAGAI SEKTOR BASIS DI PROVINSI JAMBI - Mara, Armen; Syarif, M (JALOW | Journal of Agribusiness and Local Wisdom, 2018)
This research entitled "Model of increasing rubber plantation production as the base sector in Jambi Province". This research started from the problem of low PDRB of regency / city in Jambi Province which has the potential to produce rubber. This phenomenon is related to the low productivity of rubber plantations in Jambi Province. In terms of rubber plantation has the potential to become the base sector in the region's economy. The production improvement model developed so far is still limited to multiple linear regression models. The problem of increasing rubber plantation productivity is much more complex. Therefore, this research will develop model of increasing rubber plantation production with simultaneous equation model and analyzed by Multiple Regression Model to obtain Model of productivity improvement of rubber plantation. This study will use secondary data released by institutions and related agencies, especially BPS. Data analysis will be done with eviews application program. The results of research will be useful as information for the next author's research in order to write a dissertation that the author is carrying out. The results of this study can also be used for policy making in increasing rubber plantation productivity. The results showed that 1) The development of rubber plantation production in Jambi Province is quite rapid, that in 2001 the production amount was 239,330 tons and in 2015 the production of rubber plantation increased to 350,457 tons. The growth rate is also quite convincing, ie an average of 2.65% per year. 2) The results showed that the regression model used in data analysis is good enough so as to explain the effect of independent variables of 96%. It can be explained also that the factors of rubber plantation area and the number of rainy days have a significant influence on rubber plantation production, while the variables of rubber farmers and rubber prices do not significantly affect the production of rubber plantations in Jambi Province. 3) The results also showed that the model of rubber price increase to two independent variables, the length of asphalt road and the capacity of rubber plant. However, the regression model obtained is not good enough to explain, where the variable length of the asphalt road and the capacity of the rubber plant is only able to explain 58% to the variable of rubber price in Jambi Province.